Manajeman Sarana dan Prasarana dalam Meningkatkan Kualitas Pembelajaran Di SD Negeri 22 Kota Pagar Alam - Aisyah Putri Dea Palupi (Al Banin : Jurnal Ilmiah Pendidikan Dasar, 2024)
Thesis of Madrasah Ibtidaiyah education study program, Undergraduate Program, Tarbiyah College of Science (STIT) Pagar Alam City, Supervisor: Aisyah Putri Dea Palupi, M.Pd . This research aims to find out how facilities and infrastructure are managed which include: Planning, Procurement and Utilization. Where in this research the author chose SD Negeri 22 Kota Pagar Alam as the place to carry out research. This research is descriptive qualitative research, with data collection tools in the form of interviews, observation, and documentation. In data analysis the author uses data reduction, data presentation, and data verification. The results of the research in the planning process have been carried out by conducting needs analysis, selecting equipment and seeking or determining funds to establish a school facilities procurement program. In the procurement process by realizing the planned procurement needs, in the procurement process carried out the school has provided the facilities needed by the school for the teaching and learning process, but the infrastructure is not good enough, because there are still deficiencies in the procurement of infrastructure that supports the learning process. Furthermore, the utilization process is already underway, although it is still very simple, this is because the school building has just completed a total renovation process so that the existing infrastructure has not been maximally utilized. Based on the three indicators above, it can be concluded that SD Negeri 22 Pagar Alam City has implemented facilities and infrastructure management, although it is still quite simple to support the educational process.